Steiner degree distance indices: Chemical applicability and bounds. Issue 12 (14th March 2020) - Redžepović, Izudin; Mao, Yaping; Wang, Zhao; Furtula, Boris
Abstract: The k ‐center Steiner degree distance ( SDD k ( G )) has recently been introduced as a natural extension of the degree distance DD ( G ). In this paper, the prediction potential of SDD k ( G ) is discussed. Then, the relation between this and some other well‐known distance‐based indices of trees is derived to explain its prediction potential. Finally, the lower and upper bounds of SDD k ( G ) in terms of some other graph invariants are presented. Abstract : Quantification of the structural information of a compound is commonly carried out by molecular descriptors. They are an essential part of modeling the molecular physicochemical properties. This paper demonstrates the predictive potential of the recently introduced k‐center Steiner degree distance indices. Mathematical treatment of the derived models explains their predictive powers.